Use of Arabic Language Learning Media at MAN Aek NATAS - Dedi Sahputra Napitipulu; Muhammad Irsyad (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2024)
Arabic is one of the languages in the world, which is thought to have originated from the Arabian peninsula and has experienced certain technical developments after passing a certain period and spread widely to various countries through various factors. One factor is migration. The migration phenomenon almost occurs in various countries, including Arab migration to Indonesia. This research is a literature review (library research). Library research is research whose object is sought using various library information such as books, scientific journals, magazines, newspapers and documents. This research is different from other research which requires observation and interviews to obtain data. This research is a type of approach in qualitative research. Learning media is anything that can convey a message from the sender to the recipient. In this context, it stimulates, demands and pays attention to students' thoughts, feelings and needs to facilitate learning. Based on this, we can conclude that learning media are tools that teachers use as teaching aids. In learning interactions, teachers convey educational messages to students in the form of learning materials. Based on the explanation that we have explained, it can be concluded that Arabic language learning media is very necessary in the Arabic language learning process for delivering material. Media will be very helpful and make it easier for a teacher to deliver material and can foster student enthusiasm in the Arabic language learning process.